Dolutegravir is not associated with weight gain in antiretroviral therapy experienced geriatric patients living with HIV. (1st May 2021) - Guaraldi, Giovanni; Calza, Stefano; Milic, Jovana; Calcagno, Andrea; Focà, Emanuele; Rota, Matteo; Renzetti, Stefano; Celotti, Anna; Siano, Matteo; Celesia, Benedetto Maurizio; Piconi, Stefania; de Socio, Giuseppe Vittorio; et al.
Abstract : Objective: The aim of this study was to explore weight gain in people with HIV (PWH) at least 65 years of age who switch to a DTG based regimen (DTG-s) vs. remaining INSTI-naive (INSTI-n) on stable ART. Methods: This was a longitudinal prospective study of PWH from the GEPPO cohort. At the beginning of the observational period, participants were INSTI-naives (INSTI-n). During follow-up, they were divided in two groups: INSTI-n vs. dolutegravir-switchers (DTG-s) with no further change in ART. Body weight was assessed at baseline and at last follow-up visit. Significant weight gain was defined as an increase at least 5% of baseline weight from the first to the last visit. ART regimens were collected at each patients' visit. Kaplan–Meier curves were drawn to assess time to reach a weight gain more than 5%. Results: Out of 568 PWH (83.1% men, median age 69.5 years), 427 (75%) were INSTI-n and 141 (25%) DTG-s. After an average follow-up of 2.6 (±0.8) years, no significant change in body weight was observed both among INSTI-n [delta weight = 0.02 (±7.5), P = 0.633] and DTG-s [delta weight = −0.04 (±5.2), P = 0.755]. Weight gain was also not significantly different between study groups (9.3% in INSTI-n and 15.1% in DTG-S: P = 0.175). No significant differences in time to achieve a weight gain greater or equal than 5% of baseline weight emerged in INSTI-n vs. DTG-s ( P = 0.93), two-drug regimens (2DR) vs. three-drug regimens (3DR) ( P = 0.56) or TAF vs. TDF ( P = 0.56). Conclusion: Results from a large Italian cohort did not show a significant weight gain associated with switch to DTG in PWH 65 years of age or older. This finding emerged also when comparing 3DR vs. 2DR and TAF exposed and unexposed geriatric PWH. Abstract : Supplemental Digital Content is available in the text